Cyclic numerical analyses on wood-based in-plane retrofit solutions for existing timber floors. (October 2021) - Gubana, Alessandra; Melotto, Massimo
Highlights: A numerical model of the in-plane cyclic behaviour of timber floors was developed. Wood-based strengthening solutions, connected to the original floor, are considered. The model is validated on the basis of previous experimental data on floor samples. Different in-plane strengthening configurations can be analysed and optimized. Parametric analyses and a life-size floor example are presented as case studies. Abstract: Timber-based strengthening interventions on existing wooden floors showed great potential to improve the diaphragm response in seismic rehabilitation. This is particularly important in masonry buildings in earthquake prone areas, to achieve a global box behaviour. A numerical model able to describe the non-linear cyclic behaviour of unreinforced and reinforced floors is illustrated in the present paper. Since in strengthening interventions on timber floors made by the application of timber-based panels, the fasteners proved to be the main source of non-linearity, a proper connector element is developed as an assembly of non-linear springs. Each one describes a particular aspect of the fastener behaviour in order to consider stiffness and strength degradation during the cyclic response. The model was validated by means of experimental data, acquired in a previous test campaign or available in literature. It can be used to analyse and optimize other in-plane strengthening configurations of timber floors, changing parameters as geometry, fastener spacing, sheathing orientation, opening location. This detailed numerical model can be useful also to calibrate the simpler macro models generally used for the floors in the non-linear evaluation of seismic global behaviour of buildings. A few parametric analyses and an example of a life-size floor are also presented as case studies.